Evacuation of the population to the Astrakhan district of the Stalingrad region in 1941 – 1942 - S. S. Belousov (Гуманитарные и юридические исследования)
Introduction. The history of evacuation to the USSR during the Great Patriotic War has been studied insufficiently both in the whole country and in its individual regions. Meanwhile, the study of the experience of state-organized resettlement during the years of wars and armed conflicts enriches theoretical knowledge about the policy of the authorities in emergency circumstances, and acquires a certain practical significance in connection with forced mass population movements in the territories of certain former Soviet republics, generated to a large extent by armed conflicts. The chronological framework of the article covers the period from June 22, 1941 to the end of 1942, when the offensive of Soviet troops near Stalingrad began, so the problem of evacuation has lost its relevance.Materials and methods. The research materials are based on the documents of the State Archive of the Astrakhan region. The study was conducted on the basis of comparative-historical and genetic-historical methods of cognition.Analysis. The study highlights the chronological periods of evacuation in the Astrakhan district during the Great Patriotic War, shows the management structure of evacuation processes and the policy of the authorities, determines the number of evacuated population and exit points, identifies the national composition of internally displaced persons and the geography of settlement for arrivals.Results. Based on the results of the study, it can be concluded that the Astrakhan district was the area of reception of the evacuated population and, at the same time, eviction and transit to other regions. The evacuation was carried out in an organized manner. In the conditions of a massive influx of evacuees, the Astrakhan district faced great difficulties in receiving them and sending them to other places. They were associated with the small size of the territory, lack of social and industrial infrastructure and lack of sufficient financial resources. Therefore, it was not possible to avoid starvation and lethal cases among the evacuated, epidemiological diseases and domestic disorder.